SIFAT FISIKMEKANIK PAPAN PARTIKEL TIGA LAPIS Shorea leprosula Miq. DARI HUTAN TANAMAN - U. N. M. Mangurai, Silvia; Indrayani, Yuliati; Hardiansyah, Gusti (Universitas Tanjungpura, 2013)
The big companies which are work in the forestry field has been applying the SILIN to solve of decrease the woodsproblem. Shorea leprosulaMiq.is one species is planted by those companies, it usually called as plantation forest of S. leprosula. The aim of this research is to investigate the physical (moisture content, density, water absorption, thickness swelling) and mechanical (MOE,MOR,IB, screw holding strength) properties of three layers particleboard made from S. leprosula from plantation forest,with various density. The density consist of 0.6 gr/cm3; 0.7 gr/cm3 and 0.8 gr/cm3. Three layers particleboard were fulfil the requirement the JIS A 5908-2003, except for MOE and thickness swelling at the density of 0.6 gr/cm3. The results were indicated that the particleboard ofS.leprosula from natural forest better than plantation forest and have different, especially in terms of thickness swelling, water absorbtion and IB. Particleboards from plantation forest with the optimal density has produced with optimum density 0.7 gr/cm3, that aremoisture content7.24% ; density 0.66 gr/cm3; thickness swelling dari 26.31%; water absorption 76.34%; MOE 24781.86 kg/cm2; MOR 227.35 kg/cm2; IB 4.38 kg/cm2 ; and screw holding 77.13 kg. Key Words : Shorea leprosula Miq., particleboard three layers, density, physical properties, mechanical properties